2015
DOI: 10.3136/fstr.21.327
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Chloride on the Adsorption of Proteins from Pink Shrimp (<i>Pandalus eous</i>) onto Stainless Steel Surfaces

Abstract: Cross-contamination of protein deposits to other food products can cause serious issues in food plants, where several products might be processed using the same equipment. The key to preventing cross-contamination of foods is the thorough cleaning of work surfaces. To establish an optimum cleaning process for such equipment, understanding of the adhesion behavior of proteins on food-contact surfaces is important. This work aims to examine the effect of sodium chloride (NaCl) on the adsorption of shrimp protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…On the other hand, the effect of salt concentration is one of the main factors studied on protein adsorption, as mentioned in several studies. 23–25 As observed in Fig. 3(b) and (c), the adsorption capacities decrease as both the NaCl and KCl concentrations in the medium increase.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…On the other hand, the effect of salt concentration is one of the main factors studied on protein adsorption, as mentioned in several studies. 23–25 As observed in Fig. 3(b) and (c), the adsorption capacities decrease as both the NaCl and KCl concentrations in the medium increase.…”
Section: Resultssupporting
confidence: 53%
“…Thus, the reduced adsorbate–adsorbent electrostatic interactions can change the adsorption capacity of the protein. 27…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be due to the increase in solubility of myofibrillar proteins in presence of salt ions. Ratanasumawong et al (2015) reported that presence of NaCl during extraction of shrimp protein from a stainless steel surface slightly increased the ratio of adsorbed total protein, while that of tropomyosin, decreased. Sockalingam et al (2018) observed a reduction in number of protein bands below 40 kDa and a very low intense band at 36-38 kDa in Macrobrachium rosenbergii treated overnight in vinegar.…”
Section: Sds-page Of Pressure Cooked Shrimpsmentioning
confidence: 99%